2018
DOI: 10.1039/c7ra13348k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic degradation of Orange II in aqueous solution using diatomite-supported bimetallic Fe/Ni nanoparticles

Abstract: A functional diatomite-supported Fe/Ni nanocomposite successfully remediated Orange II contaminant in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The Fe2p 1/2 peak at 724 eV is present for Ni4Fe10 and Ni5Fe10 as-synthesized samples, indicating the presence of iron oxide and iron hydroxide species [44], [48]. The Fe2p 3/2 and Fe2p 1/2 peaks are similar for NiFe alloy nanoparticles found in literature for the treatment of azo dyes [8], [41]. The Fe2p 1/2 peaks are harder to identify from the background noise for the Ni1Fe10-Ni3.5Fe10 molar ratios for the as-synthesized samples which indicates that the samples had less Fe at the surface of the particles.…”
Section: B Characterization Of Nanoparticles Pre-and Post-aqueous Orsupporting
confidence: 70%
See 2 more Smart Citations
“…The Fe2p 1/2 peak at 724 eV is present for Ni4Fe10 and Ni5Fe10 as-synthesized samples, indicating the presence of iron oxide and iron hydroxide species [44], [48]. The Fe2p 3/2 and Fe2p 1/2 peaks are similar for NiFe alloy nanoparticles found in literature for the treatment of azo dyes [8], [41]. The Fe2p 1/2 peaks are harder to identify from the background noise for the Ni1Fe10-Ni3.5Fe10 molar ratios for the as-synthesized samples which indicates that the samples had less Fe at the surface of the particles.…”
Section: B Characterization Of Nanoparticles Pre-and Post-aqueous Orsupporting
confidence: 70%
“…% ≥ 67%) [37]- [39]. NiFe alloy nanoparticles for treating azo dye literature indicate that NiFe alloy nanoparticle structure varies for studies due to differing synthesis procedures [7], [27], [41]. There is a lack of post experimental XRD analysis to determine phase shifts in the literature.…”
Section: B Characterization Of Nanoparticles Pre-and Post-aqueous Ormentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting materials are another factor since they can deeply influence the NP size, loading, and dispersion and the activity and stability of the catalysts. Among various supporting materials, diatomite has been applied as an efficient support to disperse metal NPs and it exhibited excellent performance in some reactions. For instance, Ezzatahmadi et al applied diatomite supported bimetallic Fe/Ni NPs in oxidation of orange II in the aqueous phase and found that diatomite not only served as catalyst carrier for stabilizing and dispersing bimetallic Fe/Ni NPs but also had a synergistic effect with it, thereby resulting in increased degradation ability. Besides, Zhang et al found that Pd NPs can be anchored well on natural diatomite and presented excellent activity for the Heck and Suzuki reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically for azo dye removal and degradation, the addition of Ni has been shown to result in an increase in catalytic lifetime of up to 10 days [8] and utilization of the corrosion of Fe to enhance reduction with the formation of nickel hydride [26]. Through investigations, it has been shown that as the initial concentration of azo dye is increased, degradation becomes slower, and as the initial concentration of nanoparticles increases, azo dye degradation increases [8,[26][27][28][29][30]. Azo dye degradation with bimetallic NiFe nanoparticles has been shown to work more effectively at lower pH values [8,[26][27][28] and has shown quicker initial degradation at increased temperatures as high as 40°C [26,27].…”
Section: Introductionmentioning
confidence: 99%